2014
DOI: 10.1371/journal.pone.0102062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar on Soil Microbial Biomass after Four Years of Consecutive Application in the North China Plain

Abstract: The long term effect of biochar application on soil microbial biomass is not well understood. We measured soil microbial biomass carbon (MBC) and nitrogen (MBN) in a field experiment during a winter wheat growing season after four consecutive years of no (CK), 4.5 (B4.5) and 9.0 t biochar ha−1 yr−1 (B9.0) applied. For comparison, a treatment with wheat straw residue incorporation (SR) was also included. Results showed that biochar application increased soil MBC significantly compared to the CK treatment, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
53
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 33 publications
11
53
0
2
Order By: Relevance
“…The initial positive priming in our study can be partly explained by the addition of fresh labile C in biochar (containing 30% Alkyl-C, Table 1), serving as an energy source for the microbial community (Lehmann et al, 2011). This hypothesis was supported by the rapid increase in MBC shortly after biochar application (Table 4), which was also observed in other studies (Lehmann et al, 2011;Zhang et al, 2014). At the four-month sampling we also showed that biochar addition increased soil pH from 4.6 to 5.2 compared with the controls (Table 4).…”
Section: Biochar-induced Priming Of Soil Organic Carbon In the Plantesupporting
confidence: 86%
“…The initial positive priming in our study can be partly explained by the addition of fresh labile C in biochar (containing 30% Alkyl-C, Table 1), serving as an energy source for the microbial community (Lehmann et al, 2011). This hypothesis was supported by the rapid increase in MBC shortly after biochar application (Table 4), which was also observed in other studies (Lehmann et al, 2011;Zhang et al, 2014). At the four-month sampling we also showed that biochar addition increased soil pH from 4.6 to 5.2 compared with the controls (Table 4).…”
Section: Biochar-induced Priming Of Soil Organic Carbon In the Plantesupporting
confidence: 86%
“…The MBN significantly decreased in the AC-amended soil in all populations in our study, which is supported by other studies 93,94 . For example, Zhang et al 93 found the MBN decreased with AC addition at a rate of 4.5 t/ ha/yr in the field at most sampling dates and soil depths compared to the unamended soil treatment, whereas Zavalloni et al 95 and Dempster et al 96 found AC amendment had no significant impact on MBN. Again, AC increased soil MBC in our studies supported by Ma et al 97 and Gebhardt et al 98 whom found addition of carbon as a soil amendment significantly increased MBC and thereby, altered plant biomass.…”
Section: Discussionsupporting
confidence: 92%
“…The default value for fr_bcbiom was set so a small portion (0.05 × 0.4 = 2%; Table ) of the decomposed biochar C was partitioned to BIOM. This assumption is reasonable given experimental findings that the size of the microbial pool increases following biochar application (Clough et al ., ; Bruun et al ., ; Zhang et al ., ; Liu et al ., ). The parameters described in this section have either not been experimentally measured or have been measured for only a limited range of biochar‐soil‐weather conditions (e.g.…”
Section: Methodsmentioning
confidence: 99%